Analysing the development of the climate, land, energy, and water systems (CLEWs) modelling framework: a state-of-the-art review - Kane Alexander; Naomi Tan; Francesco Gardumi; Fernando Plazas-Nino; Kamaria Kuling; Eunice Ramos; Leigh Martindale; Vivien Foster (Environmental Research: Climate)
This comprehensive state-of-the-art literature review explores recent scientific developments in climate, land, energy, and water systems (CLEWs) modelling by systematically analysing 41 peer-reviewed studies published between 2020 and 2024. This research uncovered insights into the evolving interdisciplinary landscape, revealing various trends, such as approximately 74% of studies publishing their data as open-access and 50% employing an open-source analytical tool, or tools, in combination with open-access data. This study identified four areas of significance: (1) the connections between CLEWs and the sustainable development goals, (2) how the CLEWs framework is linked to capacity development, (3) the critical interplay between energy and water systems, and (4) the transformative potential for comprehensive system integration using the CLEWs modelling framework. By pinpointing promising research directions such as soft-linking CLEWs models with geographic information systems, applying robust decision making methodologies, adapting the CLEWs framework to the city level, and highlighting the need to assess real world impact of CLEWs research, the review provides a strategic roadmap for future interdisciplinary research. Notably, the analysis emphasised the urgent need for enhanced institutional coordination and collaborative communities of practice, particularly for open-source modelling tools like the open-source energy modelling system, to further accelerate knowledge dissemination and foster innovative, integrated approaches to complex systemic challenges.